Development of a predictive thermal model based on the equivalent source approach for SMAW welding of X70 steel pipes - Chouiter, Adel; Bidi, Lyes; Bensiali, Hadjer; Chaib, Rachid; Le Masson, Philippe (Technology audit and production reserves, 2026)
The object of the research is the scientific approach for modeling thermal phenomena during welding operations in SMAW welding of pipelines. This model can be used to calculate changes in temperature fields as well as stresses and deformations. Mastering welding processes requires an understanding of the various phenomena involved. This requires numerous tests to be carried out, which are very costly for manufacturers. The ideal solution would therefore be to develop predictive numerical models that would enable the behavior of assemblies to be analyzed. The SMAW process is used to fill a chamfer between two parts. It is therefore essential to define heat input, which can be described using the equivalent heat source approach the equivalent heat source approach. The difficulty in implementing this approach lies in estimating the various parameters of the model. To this end, it was proposed to develop a simple and robust approach, which consists of using the numerical design of experiments (NDE) method. In this research, it was decided to select four parameters from the model (rsurf_sup, rsurf_inf, r0 and λ) and four objective functions characterizing the shape of the fusion zone (Lsup, Lm, Linf, H). Preliminary results show good agreement between the direct model and the dimensions recorded on the macrographic sections, with the exception of the width of the median side of the fusion zone (Lm), where there is a significant deviation of 11.4% between the measurements and the model. Furthermore, the NDE shows that rsurf_inf is the factor that most influences Lm. Adjusting the rsurf_inf factor by 0.5 from its value at the central point changes the Lm value from 3.25 mm to 3.09 mm. This adjustment optimizes the digital model by improving it and reducing the discrepancy between the simulation and the experiment for the Lm function from 11.4% to 1.2%. The results of this research make it possible to increase the reliability of petroleum facilities (pipeline assemblies). The scientific novelty of this research lies in the implementation of a simple and robust scientific approach for optimizing non-physical parameters (equivalent heat source parameters) in the modeling of welding processes.